Adopting Indigenous Knowledge Systems to Enhance Peace Education Programs for Climate Change and Adaptation in Zimbabwe - Moyo-Nyoni, Ntombizakhe (Springer, Cham, 2022)
In Zimbabwe, like many parts of the world, climate change has triggered the occurrence of conflicts, which exacerbates social, economic and political instabilities. In response to the global climate crisis, United Nations established Sustainable Development Goal 13 (SDG 13) in 2015, which advocates for taking action against climate change. The Zimbabwean government established its climate change policy in 2016, by drawing heavily on the thirteenth Sustainable Development Goal. Enshrined in SDG 13, is a call to incorporate various knowledge systems underpinned by its unique epistemology to tackle climate change. Thus, this chapter seeks to explore the use of Indigenous Knowledge Systems (IKS) in adapting to climate change. The IKS will be tested in the Lusulu ward, Lupane District, Matabeleland North Province, Zimbabwe (“Lusulu”). Primary data was sourced from focus group discussions and individual interviews. Findings revealed that the Lusulu community utilizes indigenous practices to safeguard their environment, such as the conservation of trees and the use of natural strategies such as crop rotation and use of organic matter to replenish the land. Furthermore, with regards to relationships damaged by climate changes, the indigenes apply non-violent techniques such as negotiations, mediations and consultations, which hinge on indigenous systems. The main goal of this chapter is to trigger conversations among policymakers, peace educators and civic society organisations in Sub-Saharan Africa, on the role which IKS can play in the handling of conflicts linked to climate change and, consequently, the proper facilitation of SDG 13.